Medical assisting : - Booth, Kathryn A. (McGraw-Hill, 2014)
A Medical Assistant juggles many tasks and duties while on the job. With Medical Assisting: Administrative and Clinical Procedures with Anatomy and Physiology, students are presented with all the skills needed to be a successful Medical Assistant! Now in its fifth edition, Medical Assisting: Administrative and Clinical Procedures with Anatomy and Physiology has been revamped with up-to-date comprehensive material and new chapters for the medical assistant student focused on understanding and mastering the Medical Assistant role. The text acquaints the student with all aspects of the medical assisting profession and includes newly added exercises, videos, and simulations offering a robust learning experience!